Amygdalar involvement in respiratory dysfunction - Trevizan-Baú, Pedro; Hayes, John A.; Bolser, Donald C.; Reznikov, Leah R. (Frontiers in Physiology, 2024)
The brainstem has long been recognized as the major respiratory control center, but it has become increasingly appreciated that areas upstream of the brainstem modulate respiration and airway defensive behaviors. This review aims to define the role of the amygdala, a key temporal brain region essential for limbic function, in respiration and airway defenses. We summarize literature describing roles for the amygdala in control of respiration, swallow, cough, airway smooth muscle contraction, and mucus secretion.We emphasize the need to understand how the amygdala regulates these functions both at a local scale and network scale and identify knowledge gaps for current and future investigations. Lastly, we highlight literature suggesting that amygdala dysfunction may contribute to respiratory dysfunction.